Studi Eksperimental Mortar Polimer Berbasis Epoxy dengan Penambahan Nanosilika - Septriansyah, Verinazul; Sutama, Adji; Amanda, R.A. Siti Delima; Umari, Zuul Fitriana (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2025)
This research focuses on the development of polymer mortar using epoxy as a binder, fly ash as an additive, and nanosilica as nano-filler. The study investigates the effect of nanosilica variations on the mechanical properties of polymer mortar, specifically density and compressive strength. The research used nanosilica content variations of 0%, 1%, 2%, 3%, 4%, and 5% of the mold volume. Material composition consists of 45% sand, 17.5% epoxy, 17.5% hardener, 20% fly ash, and varying nanosilica percentages. Test results show that increasing nanosilica content decreases the density of polymer mortar from approximately 1880 kg/m³ (0% nanosilica) to 1730 kg/m³ (5% nanosilica). Meanwhile, compressive strength increases up to 2% nanosilica content with an optimum value of 60.31 MPa (an 87.3% increase compared to mortar without nanosilica), then decreases with further addition of nanosilica. The findings suggest that 2% nanosilica represents the optimum content for enhancing the mechanical performance of epoxy-based polymer mortar.